g+36=63

Simple and best practice solution for g+36=63 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for g+36=63 equation:


Simplifying
g + 36 = 63

Reorder the terms:
36 + g = 63

Solving
36 + g = 63

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-36' to each side of the equation.
36 + -36 + g = 63 + -36

Combine like terms: 36 + -36 = 0
0 + g = 63 + -36
g = 63 + -36

Combine like terms: 63 + -36 = 27
g = 27

Simplifying
g = 27

See similar equations:

| -55=f-92 | | 15-2x=7x+23 | | w-1.48=2.22 | | G(x)=36-4x^2 | | n+3=9.82 | | 3b=-1.2 | | g+195=780 | | g+195=70 | | (5-w)(4w-9)=0 | | -30p=-810 | | g+-49=-70 | | b+7.98=19.98 | | -4f=14 | | 3q=14.52 | | h+7.52=18.89 | | -3(2x-4)=-14 | | 4g=17.6 | | h=5k+6fork | | 8z-5= | | 727=s+613 | | 17j=493 | | (x-y)(x^2-2xy^2+y^2)= | | 11+7lnx=9 | | 4(-2)*+8(-2)+3(-2)+6= | | -24z=408 | | v+85=937 | | 2c+3d=e+5forc | | 3x^2-x^3=0 | | -18d=-648 | | -849=b+-398 | | -83=t+390 | | -3v=13.2 |

Equations solver categories